Letter from August Friedrich Horstmann to Georg Bredig - Horstmann, August Friedrich (1912)
Thank you from August Friedrich Horstmann (1842-1929) to Georg Bredig (1868-1944) in response to birthday wishes. Horstmann expressed how much he appreciated the congratulations that were extended to him.
Keywords: Horstmann, August Friedrich, 1842-1929; Bredig, Georg, 1868-1944; Chemists